EFFECTS OF DIETARY SUPPLEMENTATION OF BACTERIOPHAGE ON CARCASS CHARACTERISTICS OF E. coli CHALLENGED COMMERCIAL BROILERS - Gotarane Himali Kishor; P. Veeramani; R. Richard Churchil; P. Raja (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A biological trial was conducted to investigate the effect of bacteriophage on carcass characteristics of commercial broilers with or without bacterial challenge. Totally 180 day old Vencobb broiler chicks were randomly allotted into five dietary treatments designated as T1 to T5 with each treatment replicated thrice. T1 and T2 served as negative and positive control respectively, while birds in T3, T4 and T5 were exposed to E. coli on different days during 35 days course. Dietary treatments included T1 - basal diet, T2 - basal diet with bacteriophage in feed (50 mg/bird/ day up to 7th day and 25 mg/bird/day up to 35th day), T3 without bacteriophage, T4-bacteriophage in feed (50 mg/bird/day up to 35th day) and T5 - bacteriophage in feed (50 mg/bird/day up to 7th day and 25mg/bird/ day up to 35th day). E. coli was introduced orally in groups T3 and T4 on day 10, while T5 on day 26 (106 CFU/ bird). The bacteriophage supplementation to E. coli challenged birds had significantly increased the weights of eviscerated carcass, giblets, ready-to-cook meat; the cut-up parts like breast, back and drumstick compared to non-supplemented group. Results shed light on the potential benefits of bacteriophage as a natural alternate approach to antibiotic growth promotors in broiler production.